Transcriptome and metabolome profiling of the medicinal plant Veratrum mengtzeanum reveal key components of the alkaloid biosynthesis - Liu, Jiajia; Han, Lijun; Li, Guodong; Zhang, Aili; Liu, Xiaoli; Zhao, Mingzhi (Frontiers in Genetics, 2023)
Veratrum mengtzeanum is a major ingredient for the Chinese folk medicine known as "Pimacao" due to the presence of unique alkaloids. Alkaloids are a diverse class of plant-specific metabolites having key pharmacological activities. There are limited studies on alkaloid synthesis and their metabolic pathways in plants. In order to elucidate the alkaloid pathway and identify novel biosynthetic enzymes and compounds in V. mengtzeanum, transcriptome and metabolome profiling has been conducted in leaves and roots. The transcriptome of V. mengtzeanum leaves and roots yielded 190,161 unigenes, of which 33,942 genes expressed differentially (DEGs) in both tissues. Three enriched regulatory pathways (isoquinoline alkaloid biosynthesis, indole alkaloid biosynthesis and tropane, piperidine and pyridine alkaloid biosynthesis) and a significant number of genes such as AED3-like, A4U43, 21kDa protein-like, 3-O-glycotransferase 2-like, AtDIR19, MST4, CASP-like protein 1D1 were discovered in association with the biosynthesis of alkaloids in leaves and roots. Some transcription factor families, i.e., AP2/ERF, GRAS, NAC, bHLH, MYB-related, C3H, FARI, WRKY, HB-HD-ZIP, C2H2, and bZIP were also found to have a prominent role in regulating the synthesis of alkaloids and steroidal alkaloids in the leaves and roots of V. mengtzeanum. The metabolome analysis revealed 74 significantly accumulated metabolites with 55 differentially accumulated in leaves compared to root tissues. Out of 74 metabolites, 18 alkaloids were found to be highly accumulated in the roots. A novel alkaloid compound viz; 3-Vanilloylygadenine was discovered in root samples. Conjoint analysis of transcriptome and metabolome studies have also highlighted some potential genes involved in the regulation and transport of alkaloid compounds. Here, we have presented a comprehensive metabolic and transcriptome profiling of V. mengtzeanum tissues. Previously, only the roots were reported as a rich source of alkaloid biosynthesis. The current findings revealed leaves and roots as significant manufacturing factories for alkaloid biosynthesis.